2022
DOI: 10.3390/toxics10050217
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk Assessment of Ortho-Toluidine Utilising Human Biomonitoring Data of Workers and the General Population

Abstract: The aim of this work was to demonstrate how human biomonitoring (HBM) data can be used to assess cancer risks for workers and the general population. Ortho-toluidine, OT (CAS 95-53-4) is an aniline derivative which is an animal and human carcinogen and may cause methemoglobinemia. OT is used as a curing agent in epoxy resins and as intermediate in producing herbicides, dyes, and rubber chemicals. A risk assessment was performed for OT by using existing HBM studies. The urinary mass-balance methodology and gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…), facilitating in a transparent manner the risk assessment process. The above method has been effectively applied for the risk assessment of bisphenols ( Sarigiannis et al, 2016 ; Sarigiannis et al, 2019 ) and ortho-toloudine ( Huuskonen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…), facilitating in a transparent manner the risk assessment process. The above method has been effectively applied for the risk assessment of bisphenols ( Sarigiannis et al, 2016 ; Sarigiannis et al, 2019 ) and ortho-toloudine ( Huuskonen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…They also highlighted the need for more robust exposure data on BP-3 and other cosmetic ingredients, and a standardized framework for incorporating HBM data in the risk assessment of cosmetic products. In the same way, Huuskonen et al (2022) [ 10 ] demonstrated, by using the example of ortho-toludine, how HBM data can be used to assess cancer risks for workers and the general population. The urinary mass-balance methodology and generic exposure reconstruction PBPK modelling were both used to estimate the external intake levels corresponding to the observed urinary levels.…”
mentioning
confidence: 98%